Evaluation of Xanthine Oxidase Inhibitory Activities in vitro of Gomphrena CelosiodesMart - Thu, Dang Kim; Hoa, Vu Thi; Khanh, Chu Ngoc; Tung, Bui Thanh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2DO - 10.25073/2588-1132/vnumps.4080, 2017)
Xanthine oxidase (XO) is an enzyme that has an improtant role in the synthesis of uric acid. XO is an enzyme allowscatalyzing the hydroxylation of hypoxanthine to xanthine and xanthine to uric acid. These are two reactions in the final stage of metabolism of the purines in the body. Offal, XO enzyme inhibitors reduce biosynthesis of uric acid have been used to prevent and treat gout. In this study , Gompherena celosiodes is extracted by ultrasonic with ethanol 80 % (EtOH)solvents and fractionated with n-hexane, ethyl acetate (EtOAc) and n-butanol (n-BuOH) solvents. These fractions were evaluated xanthine oxidase inhibitory activities in vitro . The results show that n-BuOH fraction from roots bark had the strongest XO enzyme inhibitory activity (IC 50 : 27,39 ± 0,31µg/mL), followed by EtOH fraction (IC 50 : 47,37 ± 0,26 µg/mL) and EtOAc fraction (IC 50 : 33,36 ± 0,51µg/mL) and the lowest is n-hexan fraction (IC 50 : 81,59 ± 0,21µg/mL). The research results indicated that the n-BuOH fraction and the EtOAc fraction from tree-hatched soil have a potential in the prevention and treatment of gout.